Hydration mechanism of solid waste-based artificial stone prepared by hot pressing. (28th November 2022) - Duan, Dedan; Liao, Hongqiang; Song, Huiping; Cheng, Fangqin
Highlights: The CFBFA-CS-DG ternary composite gelling system can be applied to the preparation of artificial stone. The compressive strength of the solid-waste-based artificial stone could reach 103.5 MPa at a pressure of 20 MPa, temperature of 90 °C and pressure-stabilising time of 4 h. The hot pressing (HP) helps to improve the hydration reaction. Abstract: In order to alleviate the pressure on the environment caused by natural stone mining, for large-scale and high-value utilisation of industrial solid waste and to reduce the production cost of artificial stone, in this study, a solid-waste-based artificial stone was prepared by hot pressing (HP), and the influence of pressing temperature, pressure and pressure-stabilising time on the hydration of the stone were investigated. Using circulating fluidised bed fly ash (CFBFA), carbide slag (CS) and flue gas desulfurisation gypsum (DG) as raw materials, the compressive strength of the solid-waste-based artificial stone could reach 103.5 MPa at a pressure of 20 MPa, temperature of 90 °C and pressure-stabilising time of 4 h, which meets the GB/T 9966.1-2020 'Natural Stone test Methods' compressive strength standard.